Simulation of Active Twist Rotor Blades using a Thermal Analogy Method in HMB3 - Steininger, R.; Barakos, G.N.; Woodgate, M.A. (My University, 2023)
Helicopters vibration is a well-documented area with the main rotor identified as a key source. A proposed mitigation is based on active rotor blade twist. This promises a reduction in noise and vibration, specially via avoidance of BVI effects, and has some potential for power reduction. For the development and certification of such devices, there is a need to accurately simulate the twist actuators, and rotor structure within a high-fidelity CFD framework. Two structural modelling approaches for rotors in forward flight are compared in this work. A conventional, one-dimensional, beam model is typical, where the static and dynamic twist is applied via rigid rotations on the blade. The second approach uses a medium-fidelity structural model made of 3D elements, where the active twist piezoelectric actuators are modelled via a thermal analogy method. This work presents a comparison of the two approaches.
Keywords: Aerodynamics